å¤ç”¸å›½ç«‹ç¬¬8ä¸ä¸“VISUAL COMMUNICATION DESIGNä¸“ä¸šäºŒå¹´çº§å¦ç”Ÿå¯¹å¦ä¹ æ±‰è¯å…´è¶£çš„ç ”ç©¶åˆ†æž - Ula, Rohmatul; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to find out the level of learning motivation as well as the factors contributing to learning motivation. The research subjects were the students of SMKN 8 Pontianak. In this research, the writer used interview technique, questionnaire technique, and library research method in pursuing the aforementioned research purposes. The findings of the research revealed that students? learning motivation level were still very low (171.2). Two factors that are affecting learning motivation consist of internal and external factor. Internal factor consists of expectation, attention, and joyfulness in learning. External factor consists of family background, society background, and school environment. Even though external factor has also contributed to students? learning motivation, it was found that internal factor has more significant effect on students? learning motivation. This was proven by the low-level motivation which was caused by the lack of expectation, attention in studying Chinese language as well as the lack of joyfulness in learning. Keywords: External Factor, Internal Factor, Learning Motivation